Trilingual Joyce The Anna Livia Variations - O'Neill, Patrick (University of Toronto Press, 2018)
Trilingual Joyce is a detailed comparative study of James Joyce's personal involvement in both French and Italian translations of the iconic 1928 text Anna Livia Plurabelle, which later became the eighth chapter of Finnegans Wake. Considered to be completely untranslatable at the time of its publication, the translation of Anna Livia Plurabelle represented a fascinating challenge to Joyce, who collaborated in experimental renderings of the text, first into French and later into Italian. Patrick O'Neill's Trilingual Joyce is the first comparative study of all three of the Anna Livia Plurabelle variations, and fills a long-standing gap in Joyce studies. O'Neill, an Irish-born professor who has written widely on texts in translation, also discusses in detail the avant-guard novelist and playwright Samuel Beckett's contribution as a young man to the French rendering of Anna Livia Plurabelle